Comparative company law - Gerner-Beuerle, Carsten; Schillig, Michael (Oxford : Oxford University Press, 2019)
This title features a comprehensive comparative analysis of company law in the UK, US, France and Germany. The book covers the lifespan of a company, from formation to eventual dissolution, and offers detailed explanations of each stage alongside extracts from important court decisions that show how the law works in practice in each jurisdiction.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on May 10, 2019).
Keywords: Corporation law; Comparative law